Current issues in adjuvant chemotherapy for resected, stage IB non-small-cell lung cancer. (February 2009) - Borghaei, Hossein; Mehra, Ranee; Simon, George
Evaluation of: Strauss GM, Herndon JE 2nd, Maddaus MA et al. : Adjuvant paclitaxel plus carboplatin compared with observation in stage IB non-small-cell lung cancer: CALGB 9633 with the Cancer and Leukemia Group B, Radiation Therapy Oncology Group, and North Central Cancer Treatment Group Study Groups. J. Clin. Oncol . 26, 5043––5051 (2008) . The CALGB 9633 study was designed to evaluate the efficacy of carboplatin and paclitaxel given in the adjuvant setting to patients with Stage IB non-small-cell lung cancer. Although interim analysis had shown clinical benefit, longer follow-up revealed lack of efficacy for this approach. We will examine the results of this trial in light of other positive adjuvant trials in patients with non-small-cell lung cancer.